Pengaruh Literasi Keuangan dan Financial Technology (Fintech) Terhadap Pengelolaan Keuangan pada Pelaku UMKM di Desa Mekar Bhuwana, Kecamatan Abiansemal - Ni Ketut Sukanti; Putu Gede Denny Herlambang; Ni Luh Dewi Yanti (Institut Nalanda, 2024)
The rapid development of businesses corresponds with the growing needs of society. Micro, Small, and Medium Enterprises (MSMEs) represent a sector capable of offering a diverse array of products and services and play a crucial role in providing job opportunities as a solution to unemployment problems. This study focuses on MSME owners in the Mekar Bhuwana Village, Abiansemal District. According to records from the Mekar Bhuwana Village Office in 2023, there are 194 MSMEs from various industries. The aim of this research is to evaluate the influence of financial literacy and financial technology on financial management. The study population includes MSME owners in Mekar Bhuwana Village, Abiansemal District, with a sample size of 66 respondents. The data analysis methods used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Coefficient of Determination, t-Test, and F-Test. The results of the study show that financial literacy and financial technology together have a significant impact on financial management; financial literacy significantly positively affects financial management, and financial technology also significantly positively influences financial management.